Analisis Kemampuan Berpikir Kritis Siswa Melalui Pembelajaran E-Modul IPA Berbasis Google Sites: Indonesia - Mulya Dwi Putra; Imesta Zulfanida Ernest; Muhamad Arif Nur Rokhman; Rilo Pangastuti; Insih Wilujeng; Sri Rejeki (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills are rarely measured in science learning. This study aims to analyze students' critical thinking skills through learning science e-modules based on Google sites. This type of research includes quantitative descriptive research. The subjects of this study were class VII students of SMP Negeri 6 Yogyakarta, totaling 61 students. The data collection technique used essay questions on critical thinking skills which totaled 7 items. The results showed that the identifying indicators had an achievement of 66.39% in the medium category, interpreting indicators had an achievement of 61.75% in the low category, indicators analyzing had an achievement of 69.26% in the medium category, indicators expressing opinions or arguments had an achievement of 69.26% 73.36% in the high category, the evaluating indicator has an achievement of 58.61% in the low category, and the indicator concludes that it has an achievement of 63.93% in the medium category. Thus the average students' critical thinking skills as a whole are in the medium category with an achievement percentage of 64.43%.